Spectrochemical and biochemical assay comparison study of the healing effect of the Aloe vera and Hypericum perforatum loaded nanofiber dressings on diabetic wound - ÖZBEYLİ, DİLEK; ŞENER, GÖKSEL (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Diabetic wounds have a slow healing process and easy to be infected. In addition to current drug treatments, supportive approaches are needed for diabetic wound treatment. In this study, we aimed to load Aloe Vera (AV) and Hypericum perforatum oil (HPO) with PCL/Ge (Poly (e-caprolactone)/Gelatine) polymeric biodegradable by electrospinning method into nanofiber dressings on an experimental diabetic wound model to compare the diabetic wound healing effect. Changes in the amount and chemical structure of phospholipids, proteins, and lipids were investigated in the blood and serum samples of the animals using Fourier transform infrared (FTIR) analysis. To evaluate biological events associated with the wound repair process in inflammatory phase we used oxidant and antioxidant status to determine the healing status of wounds such as Total antioxidant status (TAS), Total oxidant level (TOS) and tumor necrosis factor alpha (TNF-alpha) levels. TOS level increased in DM groups and decreased in the AV and HPO group. Oxidative stress index decreased and TNF-alpha level increased in the HPO group. FTIR spectra showed changes in the phospholipids, proteins, and carbon chain of lipids in the whole blood as well as serum of DM rats. FTIR spectra combined with Principal component analysis (PCA) showed, that treated DM rats by AV and HPO caused return chemical structure of blood and serum to this observed in control group. Higher similarity with control group for HPO rats was observed. HPO is better than AV in the alternative for healing on diabetic wound. Thus, we have demonstrated that IR spectroscopy and mul-tivariate data analysis and biochemical assays are consistent and correlative with each other. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Diabetic wound healing; Inflammation; Polymeric nanofibers dressings; Aloe vera extract; Hypericum perforatum oil; FTIR analysis; Biochemical assays; SPECTROSCOPIC TECHNIQUES; ANTIBACTERIAL ACTIVITY; QUANTITATIVE CHANGES; MEDICINAL-PLANTS; PHOSPHOLIPIDS; REGENERATION